Photocatalytic and magnetic properties of two Ni(II) metal–organic complexes based on 6, 6′-di(benzimidazol-2-yl)-2, 2′-bipyridine. (15th March 2023) - Xu, Cungang; Luo, Rong; Xie, Chenze; Fan, Chuanbin; Fan, Yuhua; Zhang, Xia
Graphical abstract: Two novel Ni(II)-based monomeric complexes are applied to the UV-light-driven degradation of methyl violet (MV). Abstract: Two Ni(II)-based monomeric complexes with the formulas of [Ni(dbb)(H2 O)2 ] (1 ) and [Ni2 (H2 dbb)2 (xda)(H2 O)2 ] (2 ) (H2 dbb = 6, 6′-di(benzimidazol-2-yl)-2, 2′-bipyridine, H4 xda = 5, 5′-(1, 4-xylylenediamino) diisophthalic acid) have been successfully synthesized under solvothermal conditions. Structural analysis revealed that the discrete monomers of 1 and 2 extend into high-dimensional networks through intermolecular hydrogen bonds, π···π stacking interactions and weak intermolecular interactions. As novel photocatalyst materials, 1 and 2 exhibited active performance towards the degradation of methyl violet (MV) under UV irradiation. Besides, the cyclic experiments indicated that 2 was stable and reusable, enabling it to be potential candidates for dye-containing wastewater treatment. The possible mechanism of the photocatalytic performance was also investigated in detail. Moreover, the magnetic susceptibility measurements of 1 and 2 demonstrated that week antiferromagnetic interactions were operative between the Ni(II) ions.